Answer:
![x=0\text{ or }x=-3\text{ or }x=3](https://img.qammunity.org/2020/formulas/mathematics/high-school/vaj5k1inz5oglsxg8hg27jajm43b5ud4rc.png)
Explanation:
We have been an equation
. We are asked to find the solutions for our given equation.
First of all, we will subtract
from both sides as:
![4x^3-36x=36x-36x](https://img.qammunity.org/2020/formulas/mathematics/high-school/ch8kuiurazs5jg2mscsj4jusyhez77qa3p.png)
![4x^3-36x=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/64k501xzt0ee4ubu2e15gmzrwetcrgs1av.png)
Let us factor the given equation.
![4x(x^2-9)=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/samo8ezr355d55pc1bfh3pqwboreivossp.png)
Use difference of squares:
![4x(x^2-3^2)=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/l5qop76t08ulwgcrrt7j41z2yvy91laf3d.png)
![4x(x+3)(x-3)=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/dfhf5jhdr9copcunhkck33iujkjzgqb155.png)
Using zero product property, we will get:
![4x=0\text{ or }(x+3)=0\text{ or }(x-3)=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/wvi2i6yjbw00ape4sur8caev4hx5vc9dn8.png)
![x=0\text{ or }x=-3\text{ or }x=3](https://img.qammunity.org/2020/formulas/mathematics/high-school/vaj5k1inz5oglsxg8hg27jajm43b5ud4rc.png)
Therefore, the solutions for our given equation would be
.